2021
DOI: 10.1007/s00299-021-02811-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles for pattern molecule of PAMP-triggered immunity in improving crop cold tolerance

Abstract: Pathogen infection cross-activates cold response and increase cold tolerance of host plants. However it is not possible to use the infection to increase cold tolerance of eld plants. Here agellin 22 ( g22), the most widely-studied PAMP, was used to mimic the pathogen infection to cross-activate cold response.Flg22 treatment alleviated the injury caused by freezing in Arabidopsis, oilseed and tobacco. In Arabidopsis, g22 activated the expression of immunity and cold-related genes. Moreover the g22 induced allev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, under freezing temperature, much more genes were found to be very highly significantly enriched in very different pathways from cold acclimation (Figure 5). These enriched pathways have also been found involving in responses to freezing stress in previous studies, such as the "MAPK signaling pathwayplant" pathway for cold signal transduction (Guo et al, 2018), the "plant-pathogen interaction" pathway for defense responses (Zarattini et al, 2021;Jin et al, 2022), and the "phenylpropanoid biosynthesis" pathway for the synthesis of important secondary metabolites (Dong and Lin, 2021). Most of the genes significantly enriched in these pathways were up-regulated to the highest levels of expression under freezing temperature in this study (Figure S7).…”
Section: Differences In Genes Associated With Cold Acclimation and Fr...mentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, under freezing temperature, much more genes were found to be very highly significantly enriched in very different pathways from cold acclimation (Figure 5). These enriched pathways have also been found involving in responses to freezing stress in previous studies, such as the "MAPK signaling pathwayplant" pathway for cold signal transduction (Guo et al, 2018), the "plant-pathogen interaction" pathway for defense responses (Zarattini et al, 2021;Jin et al, 2022), and the "phenylpropanoid biosynthesis" pathway for the synthesis of important secondary metabolites (Dong and Lin, 2021). Most of the genes significantly enriched in these pathways were up-regulated to the highest levels of expression under freezing temperature in this study (Figure S7).…”
Section: Differences In Genes Associated With Cold Acclimation and Fr...mentioning
confidence: 59%
“…A recent study showed that pathways activated by flg22 could not only help plants defend against pathogen infection, but also induce expression of cold tolerance related genes to alleviate cold injury and enhance cold tolerance (Jin et al, 2022). In plant cells, flg22 is recognized by FLS2, and activates a mitogen-activated protein kinase (MAPK) cascade to promote the expression of downstream related genes (Zipfel et al, 2004), such as WRKY33 and PR1.…”
Section: Important Roles Of Flg22 Ca 2+ and Gibberellin Signal Transd...mentioning
confidence: 99%
“…Flagellin 22 (flg22), as a conserved molecule pathogen-associated pattern, can trigger innate immune responses in plants [ 58 ]. After flg22 treatment, the accumulation of ROS and callose deposition in Col-WT leaves were continuously increased from 24 h to 72 h, and these responses were even stronger in the HbRPW8-a overexpression lines ( Figure 6 a–d).…”
Section: Resultsmentioning
confidence: 99%